Analisis Framing dalam Riset Public Relations - Prastya, Narayana Mahendra (Universitas Negeri Yogyakarta, 2016)
This paper aims to give description about how to use frame analysis in Public Relations (PR) research. The author use two framing models: Entman and Pan & Kosicki. The object is organization official statement about particular issue. Frame analysis method rarely used in Public Relations research. This methods commonly use in journalism study, to analyse the news in media. Meanwhile, the key word of framing is the social construction of reality. Organization can make social construction of realty in their official statement. In acacemic term, frame analysis in PR research is useful to know how organization positioned themselves in particular situation. Other benefit is use to evaluat whether the organization frame is conformable with the public opinion or agenda setting media or not. In practical term, frame analysis give benefit for PR practitioner to create the message that can be undserstood by public, also give positive image for organization.